The Potential Application of Giant Reed (Arundo donax) in Ecological Remediation - Zhang, Deng; Jiang, QianWen; Liang, DanYang; Huang, Shixun; Liao, Jianxiong (Frontiers in Environmental Science, 2021)
Giant reed is known as one of the most important energy plants as a consequence of its huge dry biomass production. It can be used for bioenergy or biopolymer production. Thus, it can replace maize and reduce the production cost of biomass and electricity. Giant reed and its products have different uses in industry. The use of giant reed as a raw material to obtain cellulose past for the production of rayon viscose and paper. Thanks to the flexible and strong of the material, giant reed can be used in the manufacture of fishing rods, brass musical instruments, canes and construction supplies. One of the most important characteristics of giant reed is that it shows strong growth capability in different soils with wide ranges of pH, salinity and high heavy metal contents and can be used for ecological remediation. Giant reed was able not only to decontaminate polluted soils with heavy metals, but also to purify the wastewater and decrease the pH and make red mud safer. Here, we review the available evidence regarding the utilization of giant reed in the field of phytoremediation and discuss the potential application of giant reed combined with advanced remediation technologies in ecological remediation.